2022
DOI: 10.1002/hbm.26123
|View full text |Cite
|
Sign up to set email alerts
|

Seeing and extrapolating motion trajectories share common informative activation patterns in primary visual cortex

Abstract: The natural environment is dynamic and moving objects become constantly occluded, engaging the brain in a challenging completion process to estimate where and when the object might reappear. Although motion extrapolation is critical in daily life—imagine crossing the street while an approaching car is occluded by a larger standing vehicle—its neural underpinnings are still not well understood. While the engagement of low‐level visual cortex during dynamic occlusion has been postulated, most of the previous gro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 92 publications
(110 reference statements)
4
7
1
Order By: Relevance
“…First, we observed that representational patterns of activity from the visible phase could be used to decode patterns from the occluded phase in upper and lower V1, thereby extending the results from the univariate analyses, where we only found effects in upper V1. Our results suggest that visible and extrapolated types of information share similar representational pattern in the very same voxels, replicating the results from our previous study (Agostino et al 2023). The appropriateness of the sphere selection approach that we used was further confirmed by computing the overlap of sphere centres.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…First, we observed that representational patterns of activity from the visible phase could be used to decode patterns from the occluded phase in upper and lower V1, thereby extending the results from the univariate analyses, where we only found effects in upper V1. Our results suggest that visible and extrapolated types of information share similar representational pattern in the very same voxels, replicating the results from our previous study (Agostino et al 2023). The appropriateness of the sphere selection approach that we used was further confirmed by computing the overlap of sphere centres.…”
Section: Discussionsupporting
confidence: 91%
“…Reaction time results during visible stimulation showed that participants attempted to estimate the time-to-contact of the stimulus accordingly (faster responses during fast motion, slower responses during slow motion), in HP and LP context, following the expected pattern, and corroborating the results from our first study (Agostino et al, 2023). However, we, further, observed an interaction between velocity, predictability and direction which indicated that participants responded faster to slow downward motion during the LP context.…”
Section: Behavioural Analysis Read-outssupporting
confidence: 88%
See 3 more Smart Citations